Experimental study on the mechanical properties of 1G-NPR cable anchored rock with AE-DIC method - Jiong Wang; Jian Jiang; Yiwen Chang; Haosen Wang; Lei Ma; Manchao He; Peng Liu; Siyu Wang (Rock Mechanics Bulletin)
The study investigates the mechanical properties of 1G-NPR (Negative Poisson's Ratio) cable-anchored sandstone under uniaxial compression, employing Acoustic Emission (AE) and Digital Image Correlation (DIC) methods to analyze deformation and fracture behavior. The research aims to provide insights into the failure mechanisms of rock anchored with 1G-NPR cables and their potential applications in engineering practices. A comparative analysis was performed on three anchoring methods—unanchored, conventional cable-anchored, and 1G-NPR cable anchored—under both lateral confinement and unconfined conditions during uniaxial compression. Results show that rock specimens anchored with 1G-NPR cables exhibit significantly higher uniaxial compressive strength compared to unanchored and conventional cable-anchored specimens. The 1G-NPR cables provide constant resistance at peak stress, followed by a stepped decrease in post-peak bearing capacity. Under lateral confinement, AE events are minimal in the early stage and become concentrated during the unstable crack propagation phase, accounting for around 75% of cumulative AE events. This phase features a pronounced AE activity peak at a strain level of 5.24 ​× ​10−3, the highest among the six test groups. Post-failure analysis reveals that 1G-NPR cable-anchored rock exhibits the lowest degree of fragmentation, with cracks not extending through the cable position, indicating that failure did not penetrate the cable-anchored zone. Lateral confinement aids in restricting strain concentration along the anchoring direction. DIC analysis of principal strain fields further indicates that horizontal displacement zones in 1G-NPR cable-anchored specimens emerge at 0.6Pmax at a later stage than in other groups, suggesting that these cables effectively control crack formation and propagation within the rock mass. Findings highlight the effectiveness of 1G-NPR cables in enhancing rock strength, limiting failure, and managing large deformations, thereby playing a critical role in stabilizing surrounding rock under high-ground stress in engineering applications.